(untitled) (International Journal of Nursing Education, 2026)
Background: Diabetes mellitus significantly impacts the quality of life (QoL) of older adults, particularly in rural Thailand. Beyond clinical management, caregiver support and social networks are considered to be crucial determinants of well-being. However, research regarding these factors remains limited in this specific context. This study examines the influence of caregiver, perceived social support, and QoL among elderly with type 2 diabetes mellitus. Methods: A cross-sectional study was conducted among 366 elderly patients with type 2 diabetes mellitus(aged ≥60 years). Data were collected by structured questionnaires. Multiple linear regression analyses were performed to examine associations while controlling sociodemographic and health-related variables. Results: The mean age of participants was 67.70 years (SD = 4.99), with 69.67% female. Most received care from a spouse (54.37%) or family members (28.69%), while 16.94% had no caregiver. High perceived social support(β = 0.507, p < 0.001). was associated withbetter quality of life. Similarly,family caregivers(β = 0.229, p < 0.001),spousal care(β = 0.114, p < 0.05), secondary/vocational education(β = 0.367, p < 0.001)were also associated with better quality of life. Conversely, hypertension(β = -0.153, p < 0.001), depression symptoms(β = -0.139, p < 0.05) were negative associations. Conclusion: Caregiver and perceived social support were associated with better quality of life in elderly diabetic patients in rural Thailand. These findings showed the importance of psychological management in diabetes mellitusand underscore the need for holistic, community-based interventions that establish caregiving networks and social support systems to improve well-being